2023
DOI: 10.3390/plants12122250
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Effect of Gypsum and Potassium on Nutrient Productivity in the Alfalfa–Grass Sward—A Case Study

Abstract: It was assumed that the production of alfalfa in soils naturally poor in available nutrients, such as potassium (K) and calcium (Ca), depends on the use of fertilizers. This hypothesis was validated in an experiment with an alfalfa–grass mixture carried out in 2012, 2013 and 2014 on soil formed from loamy sand that had a low content of available Ca and K. The two-factor experiment consisted of two levels of applied gypsum as a source of Ca (0, 500 kg ha−1) and five levels of PK fertilizers (absolute control, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
1
Order By: Relevance
“…Adding more Ca (basic cation) in the form of gypsum might have resulted in the fixation of more nutrients, for example, P and K [27,37], and reduction of other acidic essential trace nutrients, such as Fe, Zn, Cu and Mn [38,39], and, hence, a decrease in the forage yield. However, the findings of this research were in contrast with previous study [40], which reported the synergetic effect of gypsum and K on increasing forage yield. This may be due to a difference in the magnitudes of original Ca content in the two soils.…”
Section: Forage Yield and Nutritive Valuecontrasting
confidence: 99%
“…Adding more Ca (basic cation) in the form of gypsum might have resulted in the fixation of more nutrients, for example, P and K [27,37], and reduction of other acidic essential trace nutrients, such as Fe, Zn, Cu and Mn [38,39], and, hence, a decrease in the forage yield. However, the findings of this research were in contrast with previous study [40], which reported the synergetic effect of gypsum and K on increasing forage yield. This may be due to a difference in the magnitudes of original Ca content in the two soils.…”
Section: Forage Yield and Nutritive Valuecontrasting
confidence: 99%